Research on Roles of Mongolian Medical Warm Acupuncture in Inhibiting p38 MAPK Activation and Apoptosis of Nucleus Pulposus Cells. (9th August 2018) - Li, Sha; Bao, Lidao; Si, Lengge; Wang, Xiaohui; Bo, Agula
Abstract : Background . Mongolian medical warm acupuncture has a desirable therapeutic effect on sciatica. Apoptosis of the nucleus pulposus cells is considered to play an important role in sciatica. Evidence has demonstrated that oxidative stress and its induced activation of the signaling pathways play important roles in sciatica. However, further research is expected to reveal whether Mongolian medical warm acupuncture can inhibit the apoptosis of nucleus pulposus cells and oxidative stress. Objective . To study the effect of the p38 MAPK pathway activated by the generated ROS on apoptosis and the expression of the genes related to the balance of the extracellular matrix metabolism during treatment of sciatica with Mongolian medical warm acupuncture. Method . The volume of the active oxygen generated in the nucleus pulposus cells was detected following intervention of Mongolian medical warm acupuncture. The p38 MAPK phosphorylation level was detected with Western blot. The genes are related to the metabolism of the nucleus pulposus extracellular matrix. Result . Mongolian medical warm acupuncture reduced the active oxygen within the nucleus pulposus cells and inhibited the activation of the p38 MAPK pathway (P=0.013). Meanwhile, it upregulated the gene expression of Type II collagen, aggrecan, Sox-9, and tissue matrix metalloproteinase reagent 1 (P-0.015; P=0.025; P=0.031; P=0.045) and downregulated the gene expression of matrix metalloproteinase 3 (P=0.015). Conclusion . Mongolian medical warm acupuncture may inhibit apoptosis of nucleus pulposus cells and activation of the extracellular matrix decomposition metabolism pathway and promote its anabolism. This process may rely on the oxidative stress matrix of the p38 MAPK pathway.